Description Of Knowledge, Attitude, And Behavior At Risk Of HIV Transmission In "X" SMK Students - Desy Indra Yani; Fera Imelia Agustin; Kusman Ibrahim (Journal of Nursing Care, 2022)
HIV is a severe health problem. Pangandaran is a West Java tourist spot with a high risk of HIV transmission among adolescents. Knowledge about HIV, attitudes towards HIV transmission behavior, and HIV risk behaviors are essential for every individual because adolescents are a vulnerable population. This study aims to identify knowledge, attitudes, and risk behaviors for HIV transmission. This descriptive research with the research population is teenagers class XI and XII in SMK "X" Pangandaran, as many as 915 people. Data collection using proportionate stratified random sampling technique with a sample of 278 students online. Data collection was carried out within one month and distributed using Google Form using a modified Knowledge, Attitudes, and Risk Behavior related to HIV (PSP-HIV) questionnaire, which had been tested for validity and reliability. Data were analyzed using univariate in the form of frequency distribution for knowledge and attitudes. Risk behavior is grouped based on the frequency and percentage of respondents' answers to each statement. The results of this study found that (71.6%) of adolescents had less knowledge about HIV. A total of (54.7%) of adolescents have a terrible attitude toward HIV transmission behavior. The three risk behaviors for HIV transmission with the highest scores among students in this study were: 1) using protection or condoms during sexual intercourse as much as 5.4%; 2) having sex with girlfriends as much as 5%; 3) having sex with friends as much as 3.2%Adolescents must be provided with accurate and complete information so that they do not become a vulnerable group to suffer from HIV.